138 Pulmonary valve preservation and transannular patch techniques in children with repaired tetralogy of Fallot; echocardiographic comparison. (17th December 2020) - Avesani, Martina; Guariento, Alvise; Schiena, Chiara Anna; Reffo, Elena; Castaldi, Biagio; Padalino, Massimo; Vida, Vladimiro; Di Salvo, Giovanni
Abstract: Aims: To investigate pulmonary valve (PV) and right ventricular function by echocardiography in paediatric patients with repaired Tetralogy of Fallot (ToF), comparing PV preservation surgical strategies to standard transannular patch (TAP) repair. Methods and results: All patients undergoing transatrial-transpulmonary repair for ToF at our institution between January 2007 and May 2020 were reviewed retrospectively. Patients were divided into 2 groups, according to the different techniques used (PV preservation strategy vs TAP repair). All patients underwent standard echo-Doppler study including RV areas, fractional area change (FAC) and tricuspid annular plane systolic excursion (TAPSE); Pulmonary regurgitation (PR) was assessed by Color Doppler, continuous-wave (CW) Doppler, pressure half time (PHT) and PR index. By speckle tracking we measured also, in a subgroup of patients, right atrial strain (RAS), RV and left ventricle (LV) global longitudinal strain (RVGLS, LVGLS) and their time to peak (TTP) values. Eighty-two patients underwent a PV preservation strategy while 34 underwent a standard TAP repair. Five-year actuarial freedom from moderate/severe PV regurgitation was significantly higher in the PV preservation group compared to the TAP (61.3% [95% CI: 48-73%] vs 25.9% [95% CI: 12-43%], respectively; p = 0.02). After adjusting for age, gender, BSA, and type of PV, the use of a TAP was still significantly associated with an increased risk for PV regurgitation at Follow-up (HR: 1.85, 95% CI: 1.09, 3.15; p = 0.02). At a mean follow-up of 6.9 ± 0.3 years, patients undergoing PV preservation showed an increased right ventricular fractional area change (46.9 ± 0.8% vs 42.5 ± 1.7%, P < 0.001) and (TAPSE) z-score (-3.36 ± 0.3% vs -4.7 ± 0.4%, P = 0.005), while maintaining better PV competence in terms of pulmonary regurgitation index (87.9 ± 1.2% vs 82.7 ± 2.4%, P = 0.02). At speckle tracking subanalysis, patients undergoing PV preservation (n = 23), compared to the TAP group (n = 13) showed also higher values of RAS (37.5 ± 6.0% vs 29.3 ± 8.2%, P < 0.006), shorter right TTP (319 ± 39ms vs 357.5 ± 45.2 ms, P < 0.01) and higher values of LVGLS (-20, 6 ± 4, 2% vs -17.5 ± 3.0, P < 0.03). Conclusion: Surgical repair of ToF with PV preservation provides excellent outcomes in terms of PV competence and right ventricular function and should be advocated whenever possible.